Prenatal Diagnosis of Fetuses With Increased Nuchal Translucency by Genome Sequencing Analysis - Choy, Kwong Wai; Wang, Huilin; Shi, Mengmeng; Chen, Jingsi; Yang, Zhenjun; Zhang, Rui; Yan, Huanchen; Wang, Yanfang; Chen, Shaoyun; Chau, Matthew Hoi Kin; Cao, Ye; Chan, Olivia Y.M.; et al. (Frontiers in Genetics, 2019)
Background: Increased Nuchal Translucency (NT) is an important biomarker associated with increased risk of fetal structural anomalies. It is known to be contributed by a wide range of genetic etiologies from single nucleotide variants to those affecting millions of base-pairs. Currently, prenatal diagnosis is routinely performed by karyotyping and chromosomal microarray analysis (CMA), however, both of them have limited resolution. The diversity of the genetic etiologies warrants an integrated assay such as genome sequencing (GS) for comprehensive detection of genomic variants. Herein, we aim to evaluate the feasibility of applying GS in prenatal diagnosis for the fetuses with increased NT. Methods: We retrospectively applied GS (>30-fold) for fetuses with increased NT (≥3.5-mm), who underwent routine prenatal diagnosis. Detection of single-nucleotide variants, copy-number variants and structural rearrangements was performed simultaneously and the results were integrated for interpretation in accordance with the guidelines of the American College of Medical Genetics and Genomics. Pathogenic or likely pathogenic (P/LP) variants were selected for validation and parental confirmation, when available. Results: Overall, 50 fetuses were enrolled, including 34 cases with isolated increased NT and 16 cases with other fetal structural malformations. Routine CMA and karyotyping reported eight P/LP CNVs, yielding a diagnostic rate of 16.0% (8/50). In comparison, GS provided a 2-fold increase in diagnostic yield (32.0%, 16/50), including one mosaic turner syndrome, eight cases with microdeletions/microduplications and seven cases with P/LP point mutations. Moreover, GS identified two cryptic insertions and two inversions. Follow-up study further demonstrated the potential pathogenicity of an apparently balanced insertion which disrupted an OMIM autosomal dominant disease-causing gene at the inserted site. Conclusions: Our study demonstrates that applying GS in fetuses with increased NT can comprehensively detect and delineate the various genomic variants that are causative to the diseases. Importantly, prenatal diagnosis by GS doubled the diagnostic yield compared with routine protocols. Given a comparable turn-around-time and less DNA required, our study provides strong evidence to facilitate GS in prenatal diagnosis, particularly in fetuses with increased NT.